PRAKTIK TRANSAKSI NON TUNAI MELALUI LAYANAN SYARIAH LINKAJA PADA EKOSISTEM KEISLAMAN DI KOTA CIREBON - Nisa Lusiana; Afif Muamar; Wasman Wasman; Didi Sukardi (Fakultas Syariah Institut Agama Islam Negeri Palu, 2021)
The rise of non-cash transactions today has made people tend to switch from manual transactions that use cash to electronic transactions. LinkAja Syariah service is an application-based electronic money service designed to facilitate user transactions. LinkAja Syariah Services prioritizes three main categories of sharia service products, namely the ZISWAF, mosque-based economic empowerment and digitization of Islamic boarding schools, micro small and Medium Enterprises. Thus, this study seeks to reveal the contribution of LinkAja Sharia Services in the city of Cirebon, where the majority of the population is Muslim and there are many religious institutions. This study aims to determine the practice of using LinkAja Syariah Services in Cirebon City from an Islamic law perspective. The method used in this research is qualitative by inductive means, that is, from data to a higher level of abstraction, including synthesis and theory development (if necessary and the data supporting). This means that data analysis in qualitative research is more open-ended and must be adjusted to data in the field, such as the results of interviews, observations, and documentation. In addition, the data analysis technique used in this study was qualitative analysis as stated by Miles and Hubberman, namely data collection, data education, data presentation and conclusion drawing. The results of this study are: LinkAja Sharia services that prioritize three main products, namely the ZISWAF ecosystem, mosque-based economic empowerment, and digitization of Islamic boarding schools and UKM. In Cirebon City LinkAja Syariah services can be used for zakat, infaq and shodaqoh payments at LAZISMU Cirebon Regency, donations at At-Taqwa Mosque, and shopping at traditional markets such as Gunung Sari Market, PGC Morning Market, and Kanoman Market